Faktor – Faktor Yang Mempengaruhi Penerimaan Pajak Di Indonesia - Dissa Bramantia (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
The purpose of this study is to determine the factors that affect tax revenues in Indonesia in the long and short term. The data used in this research is secondary data obtained by BPS from the World Bank for 1991-2020. Theoretically, domestic tax revenue is influenced by various factors including Foreign Direct Investment (FDI), Gross Domestic Product (GDP), exports and imports. The analysis used is regression analysis using the Error Correction Model (ECM) method. The tests used in the model are Stationarity Test, R-Square Test, F Test and T Test. The results of this study are long-term and long-term variables, export-import variables, and GDP have a significant effect on tax revenues while FDI has no effect on tax revenues.